2017
DOI: 10.1111/1365-2664.12842
|View full text |Cite
|
Sign up to set email alerts
|

Critical catchments for freshwater biodiversity conservation in Europe: identification, prioritisation and gap analysis

Abstract: Summary The conservation of freshwater ecosystems has lagged behind that of marine and terrestrial ecosystems and often requires the integration of large‐scale approaches and transboundary considerations. This study aims to set the foundations of a spatial conservation strategy by identifying the most important catchments for the conservation of freshwater biodiversity in Europe. Using data on 1296 species of fish, mollusc, odonate and aquatic plant, and the key biodiversity area criteria (species Red List s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 37 publications
0
38
0
Order By: Relevance
“…Streams and rivers from Mediterranean-climate regions show the same trends evident in the global pattern of freshwater-biodiversity loss [126,127] that present alarming declines over the last decades, especially in mollusk and fish populations [128][129][130][131]. We suspect that the same is true for many macroinvertebrate species but the data on these taxa at the species level is generally lacking.…”
Section: Conservation Management In Mediterranean Regionsmentioning
confidence: 91%
See 1 more Smart Citation
“…Streams and rivers from Mediterranean-climate regions show the same trends evident in the global pattern of freshwater-biodiversity loss [126,127] that present alarming declines over the last decades, especially in mollusk and fish populations [128][129][130][131]. We suspect that the same is true for many macroinvertebrate species but the data on these taxa at the species level is generally lacking.…”
Section: Conservation Management In Mediterranean Regionsmentioning
confidence: 91%
“…The authors assessed the concordance of these catchments with existing protected areas and found that most high-priority catchments were inadequately covered. Likewise, Carrizo et al [131] identified priority catchments for freshwater conservation at the European scale and showed that most were located in Southern Europe and also not fully covered by existing protected areas. This is not surprising considering that the Mediterranean Basin is, among all the Mediterranean-climate regions of the world, the one with the lowest protection level [128].…”
Section: Conservation Management In Mediterranean Regionsmentioning
confidence: 99%
“…The concept of KBAs has been in use for some time (Eken et al 2004;Langhammer et al 2007), and widely employed in a number of geographical regions (e.g., Eken et al 2004;Gerlach 2008;Kasecker et al 2009;Paese et al 2010;Melovski et al 2012) and ecological zones such as freshwater ecosystems (Holland et al 2012;Carrizo et al 2014). However, a fully standardised methodology for their identification, based on a single set of criteria for all organism groups with strict quantitative thresholds-the KBA Standardhas only recently been launched .…”
Section: Alignment Of Ipa Criteria To Iucn Key Biodiversity Areasmentioning
confidence: 99%
“…for the establishment of IUCN Red Lists of threatened species (Ferrier, 2002;IUCN, 2012) or the identification of critical areas for biodiversity conservation (Carrizo et al, 2017). Furthermore, it also serves as a valuable basis for quality control of species determinations.…”
Section: Introductionmentioning
confidence: 99%